Comparing the Diagnostic Precision of Clinical Examination and MRI with Findings from Arthroscopy in Traumatic Knee Injuries with Femur or Tibia Shaft Fracture - Khaje Mozaffari 1, Javad; Moazzemian 2, Dina; Nourian 3, Javad; Zolfaghari 2, Pouneh; Ghasemian 4, Mojtaba; Shahabi 5, Zahra; Sohrabi 2*, Mohammad Bagher (Shahroud Journal of Medical Sciences, 2017)
Background: Diagnosis of knee injuries following trauma to the lower extremity is very important and needs to be carefully examined. This study aimed at comparing the diagnostic precision of clinical examination (CE) and MRI with findings from arthroscopy in traumatic knee injuries with femur or tibia shaft fracture.Methods: A cross-sectional study was conducted on 164 patients with traumatic knee injuries with femur or tibia shaft fracture who had been referred to Imam Hossein Hospital, Shahroud, between March 2014 and February 2015. We compared CE and MRI with arthroscopic findings (gold standard) to determine the concordance, accuracy, sensitivity, and specificity of injuries to the meniscus and knee ligaments.Results: The results showed that internal mucus rupture was the most common trauma, noted in 83 cases (50.6%), followed by anterior corrosion rupture, noted in 65 cases (39.6%). CE sensitivity was 68.4% and specificity was 96.2% for medial meniscal (MM) injuries, while sensitivity was 53.6% and specificity was 96.4% for lateral meniscal (LM) injuries. For anterior cruciate ligament (ACL) injuries, CE showed sensitivity of 77.2% and specificity of 91.8%. For posterior cruciate ligament (PCL) injuries, CE showed sensitivity of 52.6% and specificity of 98.6%. For MM injuries, MRI showed sensitivity of 92.5% and specificity of 86.5%, while for LM injuries, it showed sensitivity of 85.00% and specificity of 98.6%. For ACL injuries, MRI showed sensitivity of 86.7% and specificity of 93.8%, and for PCL injuries, MRI showed sensitivity of 84.5% and specificity of 98.8. For ACL injuries, the best concordance was with CE, while for MM and LM injuries, it was with MRI (P<0.001).Conclusions: Meniscal and ligament injuries in traumatic knee injury can be diagnosed through careful clinical examination, while requests for MRI can be reserved for complex or doubtful cases. CE and MRI used together have high sensitivity for ACL, PCL, and MM lesions, while for LM lesions, the specificity is higher.